Analisis Rasio Keuangan Daerah untuk Mengukur Kinerja Keuangan Pemerintah Kabupaten/Kota di Jawa Barat - Zulkarnain Zulkarnain (Institut Manajemen Wiyata Indonesia, 2020)
Measurement of the financial performance of local governments can show the financial condition of local governments and the ability of the region to explore and manage the existing sources of funds. A good regional financial performance can be seen from its effectiveness in exploring regional potentials, lower dependency on the central government, and a larger portion of PAD to finance regional development. This study seeks to measure the financial performance of the District-City Government in West Java by using a regional financial ratio measurement tool, which consists of the Fiscal Decentralization Ratio, the Regional Government Financial Dependency Ratio, the PAD Effectiveness Ratio, and the Capital Expenditure Ratio. The results of the measurement of the Fiscal Decentralization Ratio concluded that the financial capacity of the Regency-City Government in West Java is still classified as